Credibility Assessment in Asylum Claims Based on Sexual Orientation by the Greek Asylum Service: A Deep-Rooted Culture of Disbelief - Zisakou, Sophia (Frontiers in Human Dynamics, 2021)
The aim of this article is to describe and analyze the main practices that the Greek Asylum Service applies to assess credibility in asylum claims based on sexual orientation. Analysis is based on a survey of 60 cases (interviews and first instance decisions). According to the results of the survey, practices used could be divided into two categories. On the one hand practices that do not conform with refugee law, the Common European Asylum System and human rights standards, such as questions around sexual practices of the asylum seekers, stereotyped expectations about applicants’ behavior and knowledge and arbitrary assessments lacking any legal reasoning. On the other hand, practices that, at first sight, comply with international and European guidelines for credibility assessment but are based on an essentialist understanding of lesbian, gay and bisexual identity. According to the research, applicants are expected to have passed through a hard process of self-realization which has to be accompanied, by default, by feelings of difference, shame and suffering. In the article, the author critically reflects on the practices applied, concluding that this notion of sexual orientation as innate in nature that defines one’s identity, fails to take into account the intersections of gender, class, ethnicity and race and could lead to unjust judgements.